2007
DOI: 10.1016/j.taap.2007.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Human inter-individual variability in metabolism and genotoxic response to zidovudine

Abstract: A mainstay of the antiretroviral drugs used for therapy of HIV-1, zidovudine (AZT) is genotoxic and becomes incorporated into DNA. Here we explored host inter-individual variability in AZT-DNA incorporation, by AZT radioimmunoassay (RIA), using 19 different strains of normal human mammary epithelial cells (NHMECs) exposed for 24 h to 200 microM AZT. Twelve of the 19 NHMEC strains showed detectable AZT-DNA incorporation levels (16 to 259 molecules of AZT/10(6) nucleotides), while 7 NHMEC strains did not show de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…It is known that thymidine kinase 1 is expressed during S phase in hyperplastic cells, and it appears to be induced in this study by AZT treatment and is reported to be primarily responsible for AZT phosphorylation (33). From this, we propose that much higher levels of AZT-TP are present in neonatal hyperplastic heart tissue than are likely to be observed in adult tissue.…”
Section: Discussionsupporting
confidence: 53%
“…It is known that thymidine kinase 1 is expressed during S phase in hyperplastic cells, and it appears to be induced in this study by AZT treatment and is reported to be primarily responsible for AZT phosphorylation (33). From this, we propose that much higher levels of AZT-TP are present in neonatal hyperplastic heart tissue than are likely to be observed in adult tissue.…”
Section: Discussionsupporting
confidence: 53%
“…AZT (Sigma-Aldrich Co, St Louis, MO) was dissolved in phosphate buffered saline (PBS) pH 7.2 (Biosource, Rockville, MD) and the final concentration was calculated from absorbance at 266 nm with a molar extinction coefficient of 11,500. Two NHMEC strains were selected for these experiments, based on their ability to incorporate AZT into DNA [19]. Low incorporator (LI) strain M98040 cells and high incorporator (HI) strain M980005 cells were cultured for 6 passages, grown to 75% confluency and exposed in duplicate for 24 hours to 0, 10 or 200 μM AZT.…”
Section: Methodsmentioning
confidence: 99%
“…NRTI-exposed M99005 cells exhibited higher numbers of T(−) cells for all treatments when compared to NRTI-exposed M98040 cells. The data suggests that, when treated with an NRTI, the M99005 cells, which are high incorporators of AZT into DNA, are unable to properly polymerize tubulin, but the M98040 cells, which do not incorporate AZT into DNA, have normal tubulin polymerization [Olivero et al, 2008]. …”
Section: Resultsmentioning
confidence: 99%
“…These NHMEC strains have a variable ability to induce thymidine kinase 1, the first enzyme in the metabolic pathway for AZT phosphorylation. Because the M98040 cells do not induce thymidine kinase 1 and do not incorporate AZT into DNA, it is presumed that the damage is associated with inability to polymerize β-tubulin in a normal fashion after exposure to NRTIs [Olivero et al, 2008]. Although 3TC, d4T, and ddI behave in a similar fashion to AZT in halting viral transcription, 3TC and ddI are not phosphorylated by thymidine kinase 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation